Evaluating the Impact of the Pancasila Student Profile Project on Developing Student Competencies - Yustina, Yustina; Wahyuni, Resma; Suhara, Suhara; Darmawati, Darmawati; Wulandari, Putri Adita; Saputra, Rio Rasdian (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the role of education in enhancing essential competencies aligned with contemporary demands, focusing on the Strengthening Pancasila Student Profile (P5) project within Indonesia's independent curriculum. The research aims to analyze the implementation of the P5 initiative in Sekolah Penggerak in Siak Regency and its effect on students' 4C skills (collaboration, communication, critical thinking, and creativity). Employing a descriptive research design with both quantitative and qualitative approaches, data was gathered through questionnaires and interviews, then analyzed statistically. Random sampling was used to select participants. The findings indicate that teachers in Siak Regency's Sekolah Penggerak perform well, with an average score of 3.73. The P5 implementation by students is rated very highly, averaging 4.32. In terms of 4C skills, students demonstrate excellent collaboration (4.51) and communication (4.29) abilities, while their critical thinking (4.15) and creativity (4.14) are classified as good. A correlation test reveals a positive relationship between P5 implementation and the development of 4C skills.